A cautionary tale on the use of complementary therapies - Dunning, T.; Chan, S.; Hew, F.; Pendek, R.; Mohd, M.A.; Ward, G. (2001)
The use of complementary therapies is increasing. Some complementary therapies may help to stabilise, reduce or eliminate the need for diabetic medication for type 2 diabetes. Others are said to be useful in treating the symptoms of diabetic complications. However, there is a risk of adverse events with some complementary therapies, including those that arise after interaction with conventional medicines. A case study of a woman who used a Chineseherbal preparation to treat her diabetes is used to discuss some of the issues relating to the use of complementary therapies by people with diabetes.